2018
DOI: 10.2337/dc17-2210
|View full text |Cite
|
Sign up to set email alerts
|

Limb- and Person-Level Risk Factors for Lower-Limb Amputation in the Prospective Seattle Diabetic Foot Study

Abstract: Arterial disease and neuropathy emerged as the only limb-specific risk factors for amputation, but these and several person-level factors may be amenable to prevention or treatment interventions to potentially reduce diabetic amputation risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
83
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(90 citation statements)
references
References 42 publications
3
83
1
3
Order By: Relevance
“…A prediction model developed among 6440 patients with diabetic foot ulcer and based on electronic health record data found that absence of peripheral artery disease (PAD) was associated with higher probability of ulcer healing . Further support for the important role of PAD in amputation risk comes from prospective research in diabetic patients initially without foot ulcer followed prospectively, in whom an ABI ≤ 0.5 and between >0.5 and ≤0.9 were associated with hazard ratios of 3.98 and 1.88 respectively for lower limb amputation compared to an ABI between 0.9 and <1.3 . As treatments exist for PAD that may restore perfusion, the identification of diminished perfusion is highly relevant and potentially remediable .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A prediction model developed among 6440 patients with diabetic foot ulcer and based on electronic health record data found that absence of peripheral artery disease (PAD) was associated with higher probability of ulcer healing . Further support for the important role of PAD in amputation risk comes from prospective research in diabetic patients initially without foot ulcer followed prospectively, in whom an ABI ≤ 0.5 and between >0.5 and ≤0.9 were associated with hazard ratios of 3.98 and 1.88 respectively for lower limb amputation compared to an ABI between 0.9 and <1.3 . As treatments exist for PAD that may restore perfusion, the identification of diminished perfusion is highly relevant and potentially remediable .…”
Section: Introductionmentioning
confidence: 99%
“…prospectively, in whom an ABI ≤ 0.5 and between >0.5 and ≤0.9 were associated with hazard ratios of 3.98 and 1.88 respectively for lower limb amputation compared to an ABI between 0.9 and <1.3. 3 As treatments exist for PAD that may restore perfusion, the identification of diminished perfusion is highly relevant and potentially remediable. 4 This article will review clinical signs of diminished arterial perfusion and their value in the assessment of patients with diabetic foot ulcer.…”
mentioning
confidence: 99%
“…The short 13-item (RDF-13) scale may help with individualized medical decision-making and may serve as a complement to the current prediction models for lower extremity complications. [52][53][54][55] An automated item-selecting procedure ruled out the items "Tinel left" and "Right" and "MNSI-positive symptoms," meaning that they did not pass the marginal test for fitting the monotone homogeneity model. These items do not hold a robust position in the natural course of the disease, as clinicians will recognize from daily practice-patients who have had an ulcer and patients without aberrant large-fiber function (eg, intact S2PD) may still complain of painful neuropathic symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Reports of studies of large clinical cohorts were considered to identify factors most important in predicting clinical outcomes of DFU (namely, healing, major amputation, minor amputation, and/or mortality). These variables were then divided into three major groups: person related, which included presence of end‐stage renal disease, increasing age, heart failure, and nonambulatory status; limb related, which included presence of PAD, LOPS, prior minor amputation, and oedema; and ulcer related, which included area, depth, location (forefoot or hind foot), number (single or multiple), and presence of infection.…”
Section: Methodsmentioning
confidence: 99%